Restorative Justice–Informed Moral Acquaintance: Resolving the Dual Role Problem in Correctional and Forensic Practice. (January 2015) - Ward, Tony; Gannon, Theresa A.; Fortune, Clare-Ann
The issue of dual roles within forensic and correctional fields has typically been conceptualized as dissonance—experienced by practitioners—when attempting to adhere to the conflicting ethical requirements associated with client well-being and community protection. In this article, we argue that the dual role problem should be conceptualized more broadly to incorporate the relationship between the offender and their victim. We also propose that restorative justice (RJ) is able to provide a preliminary ethical framework to deal with this common ethical oversight. Furthermore, we unite the RJ framework with that of Ward's moral acquaintance model to provide a more powerful approach ( RJ-informed moral acquaintance ) aimed at addressing the ethical challenges faced by practitioners within forensic and correctional roles.